Single step synthesis and properties of M/MFe2O4 and PVDF/M/MFe2O4 (M = Co, Ni) magnetic nanocomposites - Deka, Sasanka; Joy, Pattayil Alias; Kumar, A. Pratheep (Science of Advanced Materials, 2009)
Metal/ferrite nanocomposites (M/MFe2O4; M = Co, Ni), consisting of nanoparticles of a metal and the corresponding metal ferrite, have been synthesized under in situ conditions by a simple and single step process. The metal/ferrite nanocomposites embedded in a polymer matrix have been prepared by a simple hot-pressing method. The performance parameters such as magnetization, coercivity, permeability and dielectric constant of the two- and three-phase nanocomposite systems are compared. The coercivity increases and the permeability decreases with increasing polymer content in the three-phase composite. Enhancement of the dielectric constant is observed at low frequencies.
Keywords: Dielectric; Ferrite; magnetic properties; Nanocomposite; Nanocrystalline; permeability

Superparamagnetic nanocomposite of magnetite and activated carbon for removal of dyes from waste water - Thakuria, Pankaj; Joy, Pattayil Alias (Nanoscience and Nanotechnology Letters, 2009)
Nanocomposite of superparamagnetic Fe(3)O(4) and activated carbon (AC) is synthesized at room temperature and characterized by various techniques. Magnetic measurements indicated that the Fe(3)O(4) nanoparticles are isolated by the AC particles. The magnetic fluid obtained by dispersion of the nanocomposite in water is found to be relatively stable. The dispersion is found to be very efficient for the removal of methylene blue dye from water. Thus, the nanocomposite is highly suitable for removing dissolved dyes and other contaminants from waste water by a simple magnetic separation process after adsorption on AC.
Keywords: Magnetic Separation; Nanocomposite; Superparamagnetism; Water Purification

Tuning magnetic behavior of nanoscale cobalt sulfide and its nanocomposite with an engineering thermoplastic - Rumale, Narendra; Arbuj, Sudhir S.; Umarji, Govind; Shinde, Manish; Mulik, Uttam P.; Joy, Pattayil Alias; Amalnerkar, Dinesh P. (Journal of Electronic Materials, 2015)
Nanocomposites containing magnetic nanoparticles embedded in a polymer matrix with good thermal stability (up to 200A degrees C) are technologically important. We report an environmentally benign solid-solid approach for synthesis of cobalt sulfide and its nanocomposite using a thermally stable matrix of polyphenylene sulfide. Physicochemical characterizations reveal the formation of nanoclusters of the hexagonal phase CoS. Even though bulk CoS is nonmagnetic, magnetization studies exhibit anomalous magnetic behavior for phase-pure nanoscale CoS and its nanocomposites.
Keywords: Nanocomposite; polyphenylene sulfide; Solid-solid reaction; superparamagnetic